METHODOLOGY OF OPTIMIZING SPORTS AND HEALTH PROGRAMS THROUGH SCANDINAVIAN WALKING (Scientific journal of the Fergana State University, 2024)
This article talks about the importance of Nordic walking in optimizing sports rehabilitation programs, its role in maintaining and strengthening public health, and the methodological features of popularizing this sport in our country.